Kontribusi Usahatani Jagung Pakan Mutiara (Flint Corn) Terhadap Pendapatan Rumah Tangga Petani di Desa Sambueja Kecamatan Simbang Kabupaten Maros - Emi Sulfiana; Arifin Arifin; Mohammad Anwar Sadat (Universitas Muslim Maros, 2024)
The objectives to be achieved in this study are (1) To find out the income of feed corn farming to the income of farmer households in Sambueja Village, Maros Regency (2) To find out the contribution of feed corn farming to the income of farmer households in Sambueja Village, Simbang District, Maros Regency. This research was carried out in Sambueja Village, Simbang District, Maros Regency for 2 months, namely from May to June 2024. Based on data collected from the results of the survey with the help of questionnaires with field observations/observations. The data that has been collected is then tabulated to obtain data that can be used for analysis purposes. This study uses quantitative descriptive analysis to determine the income and contribution of feed corn farmers to the household income of farmers in Sambueja Village, Simbang District, Maros Regency. Research results. This can be known through data analysis using descriptive analysis with the formula of total cost, revenue, income, and contribution so that the study results were obtained, namely the average income of feed corn farmers in Sambueja Village, Simbang District is Rp. 25,208,000/family and feed corn farmers' income contribution to farmer households in Sambueja Village, Simbang District, Maros Regency is 90.24%.